Letting Teach: Gen Z as Socio-Political Educators in an Overheated World - Biswas, Tanu (Frontiers in Political Science, 2021)
In this article, the author begins by grasping the present crisis through the social anthropological description of overheating. She then locates “Generation Z (Gen Z)” as a generation born into an overheated era and distinguishes their socio-political struggle for intergenerational climate justice from preceding generations. Following that, the author presents an analysis of the oppressive adultist dimensions of the challenges confronted by Gen Z activists like Greta Thunberg. She does so by engaging with examples from the German context. The objective of the discussion on adultism faced by Gen Z activists consequently establishes that young activists demonstrate relentless courage and hence their contribution deserves a legitimate place in rethinking socio-political “education.” Her reading reveals that young activists are simultaneously resisting adult opposition and contributing to educating older generations about the intergenerational dimensions of the climate crisis. Therefrom, the author proposes that one may re-think the matter at hand from a childist standpoint which implies a re-cognition of pupils' agency within education i.e., intergenerational relating, as something that adults can also learn from. She suggests that an integral dimension of reflexivity in further developing childist educational theory and praxis, entails a conscious commitment to letting children and youth teach adult educators too.